Improving Student Health Through PHBS Education: Strategies, Challenges, and Future Directions for Better Welfare - Ashar, Muhammad Rizki (Jurnal Riset Kualitatif dan Promosi Kesehatan, 2022)
Clean and Healthy Living Behavior (PHBS) education is an essential public health strategy for improving hygiene, nutrition, and physical activity among students. This study examines the effectiveness of PHBS educational interventions in promoting behavioral change while identifying key challenges that hinder implementation. A systematic review methodology was employed to assess relevant literature from academic databases, focusing on studies that evaluate school-based health education programs. The results indicate that structured interventions, including interactive learning, digital education, and community engagement, significantly enhance students' adherence to PHBS principles. However, barriers such as inadequate infrastructure, socio-cultural resistance, and inconsistent policy enforcement continue to limit program effectiveness. The discussion highlights the need for improved resource allocation, policy integration, and innovative educational approaches to address these challenges. Additionally, multi-sectoral collaboration among schools, health professionals, and policymakers is crucial in ensuring sustainable PHBS education. This study emphasizes the importance of integrating health education into national curricula and adopting evidence-based interventions to promote long-term behavioral change. Future research should explore scalable PHBS education models and assess their impact across diverse socio-economic settings. Strengthening PHBS education through policy support and interdisciplinary collaboration is essential in fostering a healthier generation and addressing public health concerns in educational environments.